Protein-tyrosine phosphorylation in the Archaea. - Smith, S C (1997)
Sulfolobus sulfataricus ATCC 35091, Haloferax volcanii, and Methanosarcina thermophila TM-1, representing the Euryarchaeota and Crenarchaeota subdomains of the Archaea, contain proteins which are phosphorylated on tyrosine. These data raise fundamental questions as to the origin and evolution of tyrosine phosphorylation, a protein modification that is of pivotal importance in the regulation of the physiology of eukaryotic cells.